(untitled) (World of finance, 2024)
Introduction. The development, financing, and implementation of innovative projects require the organization of effective innovation management, with the primary source of information being the accounting of innovative activities. The purpose of the article is to optimize theoretical principles and enhance the methodology of preparing and using accounting information for managing innovative activities, as well as financing innovative projects. Results. The interconnection of operational, investment, and financial activities of enterprises within the innovation environment has been substantiated, encompassing the creation, implementation, and realization of innovations. The positioning of accounting information about the operational, investment, and financial activities of enterprises in the management and financing of innovative processes has been investigated. In order to ascertain the substantive content of accounting information about the innovative activities of enterprises, a classification of its objects from the perspective of management, accounting, and financing has been carried out. For the effective accounting of diverse and variable innovative objects, the utilization of universal principles for the preparation and application of accounting information has been proposed. It has been demonstrated that adhering to fundamental provisions ensures an efficient integrated interaction between accounting, management, and financing of enterprises’ innovative activities. The distinctive features of forming and using accounting information within an integrated system of accounting and management of innovative processes have been identified. Conclusions. The effective preparation and utilization of accounting information, utilizing the provided suggestions and recommendations, in the management and financing of innovative activities ensures the realization of its goals and the attainment of positive financial outcomes. Further research is needed for the methodology of accounting for variable innovative objects with the preparation of reporting for internal and external stakeholders.